KEBEBASAN BERPENDAPAT DI LINGKUNGAN PERUMAHAN MODERN INDONESIA - Muhammad Abdiel Abrar; Muhammad Naufal Atha Al Khairi; Raihan Guntur Ramadhan; Firman Agus Budiono; Mochammad Pasha Suryatama (Universitas Nias Raya, 2025)
This study explores how freedom of expression is practiced within modern residential areas in Indonesia, focusing on the social dynamics between permanent residents and temporary renters. Using in-depth interviews as the primary method, the research captures everyday experiences related to communication, information access, and participation in neighborhood life. The findings reveal a clear information gap between these two groups, largely driven by the exclusion of renters from the main residential WhatsApp group that functions as the central communication channel. This form of information gatekeeping results in renters having limited knowledge about neighborhood meetings, community rules, social events, and collective decision-making processes. As a consequence, renters often feel disconnected and are less likely to participate in communal activities, reinforcing their marginal position within the residential environment. Although there are no explicit prohibitions against renters expressing their opinions, the lack of access to communication platforms effectively silences their voices. These challenges are compounded by minimal face-to-face interaction among residents and the physical design of cluster housing, which emphasizes privacy, boundaries, and individual ownership over shared social spaces. Such environments reduce opportunities for spontaneous interaction and dialogue, further weakening social cohesion. The study concludes that freedom of expression should not be understood merely as the absence of formal restrictions, but as a condition that requires inclusive and accessible communication structures. Therefore, the findings underscore the importance of developing more open and participatory communication mechanisms to ensure that all residents, regardless of their residential status, can engage meaningfully in community life.